PERILAKU MENYIMPANG PADA REMAJA - Laura Zeffira,; Maryeti Marwazi,; Lismawati R,; Abdul Raziq Jamil,; Ade Ariadi,; Andri Prastian Utama,; Dinda Bestari, (Nusantara Hasana Journal, 2023)
Deviant behavior is the result of an imperfect socialization process. Among teenagers, deviant behavior is often found. During adolescence, there are changes in brain structure related to emotions, judgment, behavioral organization, and self-control. There are three phases of adolescence, namely early adolescence (10-13 years old), middle adolescence (14-17 years old), and late adolescence (18-24 years old). Adolescents are prone to deviant behavior due to high curiosity, being easily influenced by the environment, wanting to stand out, wanting to be rebellious to parents, relieving boredom and stress, and unstable behavior. Deviant behavior that often occurs in adolescents is promiscuity, LGBT, and brawls. Deviant behavior has religious, social, and health impacts. Therefore, it is necessary to socialize adolescents about this deviant behavior. Socialization carried out in the form of counseling to students.